First-degree family history of cancer can be a potential risk factor among head and neck cancer patients in an isolated Mizo tribal population, northeast India - Lallianmawii Pachuau; Zothan Zami; Thanchung Nunga; R. Zodingliana; Rita Zoramthari; R. Lalnuntluanga; Zonun Sangi; Lal Rinmawii; Nachimuthu Senthil Kumar; H. Lalhruaitluanga (Elsevier, 2022)
Background: Head and Neck Squamous Cell Carcinoma (HNSCC) is commonly associated with tobacco and alcohol consumption. The aim of this study is to find the association between the risk factors with HNSCC in a small tribal population of Mizoram, North-East India. Methods: Data were obtained through consented questionnaires and Logistic Regression was used to calculate the Odds Ratio (OR) between the parameters and HNSCC. Result: Significant association was observed for smoking and alcohol with an OR of 6.703 and 4.527, respectively. The OR was found to increase with increase in smoking and alcohol consumption. Majority of the patients consumed local made alcohol and smoked the local made cigarettes known as Zozial. Moreover, the First-Degree Family History of Cancer showed a significant OR of 1.921 (95% CI: 1.040-3.547). Conclusion: Regardless of the duration of smoking or alcohol consumption, Family History of Cancer might influence the risk of HNSCC. Further screening is essential to evaluate the potential role of germline mutational effect on development of HNSCC in the population.